Mid-IR supercontinuum generation initiated by two-cascade stimulated Raman scattering in D2-filled revolver fibre. (December 2021) - Yatsenko, Yu.P.; Gladyshev, A.V.; Bufetov, I.A.
Abstract: We report a numerical study of coherent mid-IR supercontinuum generation at wavelengths above 2.4 μm, initiated by two-cascade stimulated Raman scattering in a deuterium-filled revolver fibre pumped by positively chirped picosecond pulses at a wavelength of 1.03 μm. It is shown that the highest efficiency of conversion to the second Stokes is ensured by fibre lengths at which the spectrum is strongly broadened by Kerr nonlinear effects. A range of optimal parameters (deuterium pressure, fibre length, pulse energy, and pulse duration) is found that ensure quantum efficiency at a level of 50 % and a mid-IR supercontinuum width above 1000 nm. The coherence properties of the supercontinuum are shown to be determined by the pulse duration, the magnitude of the pulse chirp, and dispersion characteristics in each transmission band of the fibre. We demonstrate the feasibility of generating a single compressed mid-IR pulse of 20-fs duration with an energy of 1.9 μJ.